Penetapan Kadar Fenolik dan Flavonoid Hasil Ultrasonic Assisted Extraction Daun Binahong (Anredera cordifolia [Ten] Steenis) - Sjahid, Landyyun Rahmawan; Aqshari, Amelia; Sediarso, Sediarso (Universitas Andalas, 2020)
Anredera cordifolia [Ten] Steenis has been proven to have pharmacological activity that is thought to be influenced by the presence of phenolic compounds and flavonoids. However, both compounds are found in small concentrations through conventional extraction (maceration, decoction, soxhlet, and reflux). This study aims to prove that the ultrasonic assisted extraction method can obtain higher concentrations of phenolic and flavonoid compounds. Dried binahong leaves were extracted using ultrasonic assisted extraction with 70% ethanol. Phenolic levels were determined using Folin-Ciocalteu, while flavonoid levels were determined using the colorimetric aluminum method. The results showed binahong leaves ethanolic extract had phenolic levels of 10.16 % GAE and flavonoid levels of 10.58 % QE. These results are much higher than the results obtained using conventional extraction so that ultrasonic assisted extraction can be recommended to maximize the extraction of phenolic and flavonoid levels from the leaves of Binahong (Anredera cordifolia [Ten] Steenis).Â